Impact of Communication in Satisfaction of Patient’s Family: Study of Healthcare Services Using PLS-SEM - Neha Bansal; Mahabir Narwal; Neeraj Chaudhary; Vivek Gupta (Journal of Health Management, 2026)
In the Indian context, family members play a crucial part in the care of patients, since they can provide psychological as well as emotional assistance to hospitalised patients. Communication is regarded as a vital clinical skill in medicine for establishing rapport with patients and their families and opening the way for effective diagnosis and therapy. A descriptive study was designed to assess the level of family satisfaction in the context of communication with doctors, nurses, administrative staff and miscellaneous staff. A sample size of 424 family members from 5 public and 5 private hospitals of Delhi-NCR was chosen, and duly filled questionnaires were collected from them. A conceptual model was developed and validated using partial least squares structural equation modelling (PLS-SEM) 4.0. Families were found to be satisfied with communication with doctors, nurses and administrative staff. Families were extremely discontented with communication with miscellaneous staff. Although miscellaneous staff play an imperative role in the development of satisfaction, the focus should be on overcoming the communication gap between the staff and the families. The present research article aims to help healthcare providers (doctors, nurses, administrative staff, managers and concerning authorities) to deal in an improved way to get rid of issues related to healthcare communication.